Radial Keratotomy Fact Sheet - ACO, CAO (Canadian Journal of Optometry, 2021)
The controversial surgical procedure called Radial Keratotomy (or RK) is now being talked about widely, not only in professional publications, but also in the public media as well. Coverage in the latter has ranged from a segment on ABC- TV's "20/20" program to local newspaper advertising by surgeons. It has prompted many patients to ask their optometrists for the facts about RK.